2016
DOI: 10.2116/analsci.32.75
|View full text |Cite
|
Sign up to set email alerts
|

Living Single Cell Analysis Platform Utilizing Microchannel, Single Cell Chamber, and Extended-nano Channel

Abstract: Single cell analysis has been of great interest in recent years. In particular, to achieve living single cell analysis is the ultimate goal to study the dynamic process of the single cell. However, single cell volume is pL in scale, and it is difficult to realize living single cell analysis, even by microfluidic technology (nL-sub nL). Herein, a novel microfluidic platform was developed by integrating a single cell chamber and an extended-nano channel (aL-fL volume). A single cell was isolated and cultured for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Eberle et al controlled the macromolecular motion in a nanochannel (width: 500 nm and depth: 200 nm) by the valve of electric potentials [ 99 ]. Another approach to detect conductivity changes is to vary the micro/nanochannel interface shape, whereas Lin et al detected differences in electrical resistance before and after connecting a living single cell and a nanochannel (width: 900 nm and depth: 900 nm) by lipid fusion which is well known as patch clump method [ 100 , 101 ]. The number of molecules were detected by determining the changes in conductivity as the analyte passes through the nanochannel.…”
Section: Electrical/electrochemical Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eberle et al controlled the macromolecular motion in a nanochannel (width: 500 nm and depth: 200 nm) by the valve of electric potentials [ 99 ]. Another approach to detect conductivity changes is to vary the micro/nanochannel interface shape, whereas Lin et al detected differences in electrical resistance before and after connecting a living single cell and a nanochannel (width: 900 nm and depth: 900 nm) by lipid fusion which is well known as patch clump method [ 100 , 101 ]. The number of molecules were detected by determining the changes in conductivity as the analyte passes through the nanochannel.…”
Section: Electrical/electrochemical Detectionmentioning
confidence: 99%
“…Eberle et al controlled the macromolecular motion in a nanochannel (width: 500 nm and depth: 200 nm) by the valve of electric potentials [99]. Another approach to detect conductivity changes is to vary the micro/nanochannel interface shape, whereas Lin et al detected differences in electrical resistance before and after connecting a living single cell and a nanochannel (width: 900 nm and depth: 900 nm) by lipid fusion which is well known as patch clump method [100,101] (width: 100 nm and depth: 100 nm) [104] detected viruses in nanochannels, and Yasaki et al (width: 2.2 µm and depth: 3.7 µm) detected bacterial cells in a microchannel [105]. In their methods, advanced analyses were achieved by integrating the pore structures in micro/nanochannels which were fabricated by top-down methods.…”
Section: Detection Based On Conductivity Measurementmentioning
confidence: 99%
“…For this purpose, Guo et al 75 developed a novel electrode-based microarray chip used for measuring the adhering behavior of a single Hela cell by detecting its impedance spectra in situ. Besides, Lin et al 76 reported an extraordinary study that monitored the living cell viability by electric resistance measurement on a novel microfluidic platform. As shown in Fig.…”
Section: •2 Electrochemical Analysismentioning
confidence: 99%
“…Zebrafish with high genomic homology to humans is a simple vertebrate model organism that offers multiple applications in fundamental and biomedical research. [74][75][76] The observation of zebrafish larvae's behavior in response to various stimuli is of interest in the field of nervous science. For instance, Peimani et al 83 developed a versatile microfluidic platform to study the rheotaxis and electrotaxis behavior of zebrafish larvae.…”
Section: Single-cell In Vivomentioning
confidence: 99%
“…Lin et al developed a novel device by integrating a single-cell chamber and an extended-nano channel. 6 This device enables one to isolate and culture single cells for more than 12 h by pressure-driven flow control. In addition, an electric resistance measurement method can monitor the cell viability without any fluorescence labeling.…”
mentioning
confidence: 99%